Fiscal decentralization and local budget deficits in Viet Nam: An empirical analysis - Peter J. Morgan; Long Q. Trinh (Asian Development Bank Institute (ADBI), 2016)
Since 1975, Viet Nam has gradually decentralized more fiscal responsibilities to local authorities. This study has two objectives: (i) to take stock of the current institutional framework for intergovernmental fiscal relations in Viet Nam, and (ii) to empirically assess the debt sustainability of local governments in Viet Nam. The empirical analysis uses two estimation methods: (i) fully modified ordinary least squares (OLS) to estimate the long-term correlations between co-integration equations, including vectors of co-integration variables, and stochastic regressor innovations; and (ii) fiscal reaction equations at the provincial level, based upon the Bohn (2008) model. The empirical results suggest that deficit levels are generally sustainable at the local level.
Keywords: H70; H71; H72; H74; H77; 330; Government decentralization; government fiscal balance; intra-government transfers; expenditure assignment; revenue assignment; local government borrowing; Viet Nam